Role of Common Fractalkine Receptor Variants with Chronic Hepatitis B Patients in Tunisia - Imene Ben Dhifallah; Kaouther Ayouni; Zeineb Belaiba; Bacem AlaDdine Razgui; Sahar Trabelsi; Henda Touzi; Amel Sadraoui; Walid Hammemi; Hela Hannachi; Amira Kebir; Slimane Ben Miled; Henda Triki (Viruses, 2025)
Chronic hepatitis B virus (CHB) infection remains a leading cause of hepatic inflammation and damage. Several studies have suggested the significant role of CX3C chemokine receptor 1 (CX3CR1) in inflammatory damages. The polymorphisms V249I and T280M affect receptor expression and function. In the current study, we investigated the association of V249I and T280M variants of the CX3CR1 fractalkine receptor with susceptibility to CHB disease. In total, 280 patients with chronic hepatitis B and 260 controls from different cities of Tunisia recruited in the Pasteur Institute of Tunisia between January 2017 and December 2022 were genotyped for the V249I and T280M CX3CR1 gene. The allele and genotype frequencies of these variants did not show significant associations with susceptibility to CHB infection (p > 0.05). Analysis of allele and genotype frequencies showed that there was no differences in age and sex distribution between patients and the control group, but when CHB patients were stratified according to age, a clear significant difference was obtained for the T280M polymorphism (p < 10−3, OR = 88.91; p < 10−3, OR = 37.42, for genotype and allelic distribution, respectively) with the MM genotype being more frequent in patients aged ≥ 50 years. The most frequently combined genotypes in the Tunisian population were VVTT, VITT and VITM both in patients (48.9%, 22.5% and 22.1%, respectively) and in controls (52%, 23.8%, 13.5%, respectively) compared to the extremely rare IITT, IITM or IIMM genotypes. In conclusion, this study suggests a noteworthy genotype–age association, particularly involving the T280M variant